Emodin attenuates systemic and liver inflammation in hyperlipidemic mice administrated with lipopolysaccharides. (August 2014) - Jia, Xuemei; Iwanowycz, Stephen; Wang, Junfeng; Saaoud, Fatma; Yu, Fang; Wang, Yuzhen; Hu, Jun; Chatterjee, Saurabh; Wang, Qian; Fan, Daping
Non-alcoholic fatty liver disease (NAFLD) is a major epidemics of the modern societies and has an inflammatory component in the pathogenesis. However, approved anti-inflammatory therapies are not currently available for the prevention of the transition from simple steatosis to non-alcoholic steatohepatitis (NASH). We aimed to test if a Chinese herb-derived compound, emodin could halt the simple steatosis to NASH transition. LDLR −/− mice were fed a western-type diet for 10 weeks; and during the last four weeks, the mice were intra-peritoneally injected daily with LPS with or without emodin. Systemic inflammation was evaluated by measurement of serum levels of cytokines and chemokines and flow cytometric analysis of spleen leukocytes. Liver inflammation was determined by histology, immunocytochemistry and flow cytometry. Quantitative real-time PCR and Western blot were performed to examine the effects of emodin on LPS-induced inflammatory responses in macrophages. Our data showed that emodin ameliorated systemic inflammation, reduced inflammatory cell infiltration in the liver, and attenuated liver function impairment. In vitro experiments showed emodin inhibited LPS-induced expression of proinflammatory cytokines in macrophages through suppressing Erk1/2 and p38 signaling. In conclusion, emodin inhibited the transition from simple steatosis to NASH in hyperlipidemic mice challenged with LPS through suppressing systemic and macrophage inflammation. Emodin may be developed as a therapy for NAFLD by the virtue of its anti-inflammatory effects.